Oral Presentations 1981
DOI: 10.1055/s-0038-1652050
|View full text |Cite
|
Sign up to set email alerts
|

Involvement Of Human Factor IX In Tissue Thromboplastin Induced Coagulation

Abstract: This study is concerned with the question whether activation of factor IX by factor VII - tissue thromboplastin contributes to the rate of plasma coagulation. The protein component of tissue factor was partially purified from human brain. Its molecular weight as deduced from SDS - polyacrylamide gel electrophoresis was about 48,000. Reconstitution of thromboplastin activity was obtained by mixing apoprotein and phospholipids in the presence of Triton X-100 and subsequent removal of Triton by adsorption to Biob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1982
1982

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our own experiments (see Table 1) and those of others (28,31) indicate that the time interval used to follow factor Xa generation is much longer than that needed for plasma coagulation. In this respect it is interesting that Van den Besselaar et al (15) reported that even at extremely low tissue factor concentrations the plasma-coagulation time is independent on the presence or absence of the intrinsic activator (factor VffI, factor D(). Flowever, at present it is still questionable which model glves the better approximation of in vivo coagulation: the generation of activated coagulation factors or plasma coagulation times.…”
Section: Intrinsic Extrinsic and Intrinsicmentioning
confidence: 99%
“…Our own experiments (see Table 1) and those of others (28,31) indicate that the time interval used to follow factor Xa generation is much longer than that needed for plasma coagulation. In this respect it is interesting that Van den Besselaar et al (15) reported that even at extremely low tissue factor concentrations the plasma-coagulation time is independent on the presence or absence of the intrinsic activator (factor VffI, factor D(). Flowever, at present it is still questionable which model glves the better approximation of in vivo coagulation: the generation of activated coagulation factors or plasma coagulation times.…”
Section: Intrinsic Extrinsic and Intrinsicmentioning
confidence: 99%
“…Thromboplastin concentration was varied by recombination of different amounts of apoprotein with a constant amount of phospholipid. Part of this study has been reported earlier in a preliminary form (6).…”
Section: Introductionmentioning
confidence: 99%